Morfometri, Morfologi Serta Abnormalitas Spermatozoa Owa Jawa (Hylobates moloch) Asal Ejakulat - Astuti, Pudji; Yusuf, Tuty Laswardi; Sajuthi, Dondin; Hayes, Eric; Budipitojo, Teguh; Sjahfirji, Luthfiralda; Maheshwari, Hera (2004)
.